1984
DOI: 10.1111/j.1751-1097.1984.tb04580.x
|View full text |Cite
|
Sign up to set email alerts
|

MODIFYING FACTORS OF THE CELLULAR CONCENTRATION OF PHOTOLYASE MOLECULES IN Saccharomyces cerevisiae—II. EFFECTS OF PREILLUMINATION WITH LIGHT FLASHES

Abstract: The effects of preillumination with photoreactivating light flashes before UV‐irradiation on the number of photoreactivable complexes consisting of UV‐induced DNA‐damages and active photolyase molecules (NPREact), on the fluence decrements, ΔDPRE, that are obtained from two UV‐survival curves without and with 1 flash photoreactivation and proportional to NPREact were determined in haploid Saccharomyces cerevisiae cells. ΔDPRE increased by preillumination from 0.115 Jm–2 to 0.460 Jm–2 and from 0.376 Jm–2 to 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that growth of S. cerevisiae cells under photoreactivating light before exposure to 254nm radiation enhances cell survival as a result of an apparent increase in the number of active photolyase molecules per cell (22)(23)(24). In contrast, we were unable to detect induction of Phrl-3-galactosidase fusion protein after exposure of dark-grown cells to fluences of photoreactivating light as great as 3 J/m2, more than 104-fold greater than the smallest fluence of 254-nm light producing reproducible induction PHRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that growth of S. cerevisiae cells under photoreactivating light before exposure to 254nm radiation enhances cell survival as a result of an apparent increase in the number of active photolyase molecules per cell (22)(23)(24). In contrast, we were unable to detect induction of Phrl-3-galactosidase fusion protein after exposure of dark-grown cells to fluences of photoreactivating light as great as 3 J/m2, more than 104-fold greater than the smallest fluence of 254-nm light producing reproducible induction PHRI.…”
Section: Discussionmentioning
confidence: 99%
“…The only known function of the enzyme is DNA repair. It has been previously reported that photolyase activity increases in vivo in response to photoreactivating light and that at least a part of this increase requires protein synthesis, suggesting that enzyme activity or concentration is regulated (22)(23)(24). Whether this increase reflects transcriptional, translational, or posttranslational modifications has been unclear, in part because a method of quantifying the number of photolyase molecules independent of photoreactivating activity was not available.…”
mentioning
confidence: 99%